24 GHz Six-Port Medical Radar for Contactless Respiration Detection and Heartbeat Monitoring - Vinci, Gabor; Lindner, Stefan; Barbon, Francesco; Hofmann, Maximilian; Fischer, Georg; Kissinger, Dietmar; Kölpin, Alexander (9th European Radar Conference, 2012)
For numerous medical applications it is of primary interest to monitor the breath rate and heartbeat of a patient over time. Especially important is to observe the respiration of a patient over night to detect potential sleep disorders. Furthermore, heartbeat frequency is also a precious informationwhich can help to improve diverse diagnosis procedures. In orderto better analyze these vital parameters an innovative contactlessrespiration detection and heartbeat monitoring technique hasbeen developed. This novel method is based on the six-portinterferometric radar and is capable of detecting breath rateas well as heartbeat frequency without applying sensors orelectrodes on the patients body.
elib2cris::1512001600,vinci2012f
Keywords: Six-Port; Bioradar; Vital Sign Monitoring; Heartbeat Detection; Respiration Detection

60 GHz industrial radar systems in silicon-germanium technology - Agethen, Roman; Pour Mousavi, Seyed Mehran; Forstner, Hans-Peter; Wojnowski, Maciej; Pressel, Klaus; Weigel, Robert; Kissinger, Dietmar (IEEE MTT-S international Microwave Symposium, 2013)
elib2cris::1512001600,agethen2013

77-GHz Automotive Radar System based on SiGe - Integrated Circuits: Current Developments and Future Trends (Invited Paper) - Kissinger, Dietmar; Starzer, Florian; Wagner, Christoph; Knapp, Herbert; Forstner, Hans-Peter; Jäger, Herbert; Maurer, Linus; Lachner, Rudolf; Weigel, Robert (Fifth Joint Symposium on Opto- and Micorelectronics Devices and Circuits, 2009)
elib2cris::1512001600,kissinger2009a

A 10 Gb/s Highly-Integrated Adaptive Pseudo-Noise Transmitter for Biomedical Applications - Schmidt, Christian; Nehring, Johannes; Dietz, Marco; Weigel, Robert; Kissinger, Dietmar; Hagelauer, Amelie Marietta (IEEE Radio and Wireless Symposium, 2017)
A highly-integrated (2^11)-1 pseudo-random bit sequence (PRBS) transmitter for biomedical applications is presented. The chip consists of an ultra-wideband synthesizer with an integrated divider to drive a PLL, a linear feedback shift register (LFSR) to generate an M-sequence and a programmable binary divider to enable adaptive subsampling technique in the signal processing path. The circuit is created to be used in a miniaturized portable PRBS based sensor system for biomedical applications. A conceivable application is the measurement of dehydration in a human body. The PRBS generator is capable of generating a bit-rate up to 10 Gb/s, correlating to a maximum bandwidth of the generated sequence of 5 GHz, which is sufficient for the designated applications. The circuit is manufactured in an 0.35 um SiGe-Bipolar technology with an ft of 200 GHz using 12 mm^2 chip area.
elib2cris::1512001600,schmidt2017

A 1.16 pJ/bit 80 Gb/s 2¹¹-1 PRBS generator in SiGe bipolar technology - Radwan, Ahmed; Talai, Armin; Weigel, Robert; Kissinger, Dietmar (9th European Microwave Integrated Circuit Conference (EuMIC), 2014)
A 211-1, 80Gb/s pseudo-random bit sequence (PRBS) generator, employing parallel architecture is presented. The generator is optimized to provide a high bit rate as well as a long sequence length without any need of inductive peaking for a lower power consumption, compared to PRBS generators reported in literature. The PRBS generator consists of two parallel complementary rows of linear feedback shift registers (LFSR), operating up to 40Gb/s, where the generated PRBS from each are multiplexed to provide a bit-rate of double the clock frequency, reaching up to 80Gb/s. The clock distribution network was carefully optimized for a reduced amplitude and phase error to push the boundaries of the maximum achievable bit-rate. The PRBS generator is capable of generating bit-rates ranging from 10Gb/s up to 80Gb/s, with a power consumption of 576 mW to 1 W. The circuit is manufactured in an 0.35 μm SiGe-Bipolar technology with an ft of 200 GHz.
elib2cris::1512001600,gharib2014b

A 122 GHz multiprobe reflectometer for dielectric sensor readout in SiGe BiCMOS technology - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Kissinger, Dietmar; Weigel, Robert (IEEE Compound Semiconductor Integrated Circuits Symposium, 2011)
elib2cris::1512001600,laemmle2011a

A 125-GHz permittivity sensor with read-out circuit in a 250-nm SiGe BiCMOS technology - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Weigel, Robert; Kissinger, Dietmar (IEEE Transactions on Microwave Theory and Techniques, 2013)
elib2cris::1512001600,laemmle2013a

A 180 GHz Frequency Multiplier in a 130 nm SiGe BiCMOS Technology - Girg, Thomas; Beck, Christopher; Dietz, Marco; Hagelauer, Amelie Marietta; Kissinger, Dietmar; Weigel, Robert (2016 IEEE 14th International NEWCAS Conference, 2016)
An integrated analog frequency multiplier for a novel high data rate communication system has been developed to multiply a 18 GHz input signal by ten to generate a 180 GHz output signal. With a first step the 18 GHz input signal is fed into a times five edge combiner, which generates an intermediate frequency of 90 GHz. Therefore five different phases with a delta of 72 degree are needed, that are provided by an active allpass filter chain. In a second step the 90 GHz intermediate frequency is given into a double-balanced Gilbert cell mixer. Here, frequency doubling is achieved by feeding the same signal into the LO and RF port of the mixer. Hence, the overall output frequency of 180 GHz results in 180 GHz with a simulated output power of -7 dBm. All simulations are done post-layout. The chip is implemented in a 130 nm BiCMOS technology with a chip area of 0.9 mm x 1 mm.
elib2cris::1512001600,girg2016
Keywords: SiGe BiCMOS; high data rate communication; 180 GHz; simultaneous phase and amplitude regenerative sampling; transmitter; frequency multiplier

A 2-30 GHz Multi-Octave Planar Microwave Six-Port for Reﬂectometry Applications - Bauch, Andreas; Hofmann, Maximilian; Nehring, Johannes; Weigel, Robert; Kissinger, Dietmar (European Microwave Conference (EuMC), 2015)
This paper presents a planar multilayer six-port circuit implementation based on multi-octave directional couplers. The presented six-port circuit is the first published six-port, that is capable of operating in an ultra-boradband frequency range from 2 to 30 GHz. Within this spectrum the six-port allows for the determination of the complex reflexion coefficient through four scalar power measurements. The six-port circuit is based on the quasi-optimal design proposed by Engen. Proper functionality has been verified through measurements of the S-parameters and the calculated q-points.
elib2cris::1512001600,bauch2015

A 33% Tuning Range High Output Power V-Band Superharmonic Coupled Quadrature VCO in SiGe Technology - Nasr, Ismail; Dudek, Manuel; Weigel, Robert; Kissinger, Dietmar (IEEE Radio Frequency Integrated Circuits Conference, 2012)
Abstract—This paper presents a wide tuning range superharmonic coupled quadrature Colpitts VCO with high output power. The circuit was fabricated using a low-cost SiGe technology with an ft/fmax of 200/250 GHz. The quadrature VCO employs a novel area efficient coupling technique that uses second harmonic coupling. Downcoversion mixers are implemented to provide an intermediate frequency signal, enabling easier measurement. A phase imbalance below 2 degrees is measured between the quadrature outputs, over a 6 GHz tuning range. The quadrature VCO can be tuned between 55 and 76.5 GHz having a record tuning range of approx. 33%. Moreover, the quadrature VCO has a maximum measured output power of +10.5dBm, and a minimum phase noise of -97 dBc/Hz. The overall chip draws 303mA from a 3.3V supply.
elib2cris::1512001600,nasr2012a
Keywords: Quadrature oscillator (QVCO); Colpitts; Wide tuning range; superharmonic coupling

A 4–32-GHz Chipset for a Highly Integrated Heterodyne Two-Port Vector Network Analyzer - Nehring, Johannes; Dietz, Marco; Aufinger, Klaus; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE Transactions on Microwave Theory and Techniques, 2016)

A 50-100-GHz Highly Integrated Octave-Bandwidth Transmitter and Receiver Chipset in 0.35um SiGe Technology - Nasr, Ismail; Knapp, Herbert; Aufinger, Klaus; Weigel, Robert; Kissinger, Dietmar (IEEE Transactions on Microwave Theory and Techniques, 2014)
This work presents a highly integrated transmitter (TX) and receiver (RX) chipset operating from 50 to 100 GHz. The local oscillator (LO) is realized using a high output power millimeter-wave integrated frequency synthesizer with an octave output frequency range. The proposed low-complexity discrete tuned synthesizer architecture employs a single wide-tuning range voltage-controlled oscillator core and a single-sideband mixer, which can be switched to operate as a LO amplifier. An ultra broadband variable gain amplifier, with a gain control range >hbox 25 dB, is used at the output of the synthesizer to provide a tunable output power. A maximum output power from +hbox7 to +hbox12 dBm and an output phase noise from -hbox83 to -hbox96 dBc/Hz at 1-MHz offset are measured over the complete output frequency range. Moreover, a spurious suppression >hbox 22 dB is achieved over the entire synthesizer's tuning range. The RX shows a conversion gain >hbox 19 dB and a noise figure < hbox 9.5 dB from 50 to 100 GHz. The TX's measured saturated output power is from +hbox6 to -hbox1 dBm over the entire frequency range. The complete chipset is realized in a commercial low-cost SiGe:C technology with an f- t/f_max of hbox170/250 GHz. Each of the TX and RX chips including the frequency synthesizers draw a current of 370 mA from a 3.3-V supply.
elib2cris::1512001600,nasr2014

A 50 to 100GHz frequency synthesizer with 17dB side-band suppression using a single VCO core - Nasr, Ismail; Weigel, Robert; Kissinger, Dietmar (The European Microwave Integrated Circuits Conference (EuMIC), 2013)
elib2cris::1512001600,nasr2013a

A 60-GHz Low-Noise Variable-Gain Amplifier in a 130-nm BiCMOS Technology for Sixport Applications - Völkel, Matthias; Dietz, Marco; Hagelauer, Amelie Marietta; Weigel, Robert; Kissinger, Dietmar (IEEE International Symposium on Circuits and Systems, 2017)
Abstract—A monolithic low noise variable gain amplifier (LNA) operating at 60 GHz is presented. It is designed for a sixport receiver, which is completely integrated on a single chip. These chips are build in highly miniaturized sensors to measure distances with radar. Therefore a high performance LNA is indispensable. The circuit has been designed using a new 0.13 m SiGe BiCMOS process from IHP (SG13G2). For implementation a three stage architecture is chosen. Measurements show a tuneable gain from 16 to 24 dB at 60 GHz, an input matching of -17 dB and an output matching of -14 dB. The circuit consumes 13mA from a 3.3V supply.

A 62 GHz reflectometer for biomedical sensor readout in SiGe BiCMOS technology - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Kissinger, Dietmar; Weigel, Robert (IEEE Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems, 2012)
elib2cris::1512001600,laemmle2012

A 70 GHz bandwidth low-power active balun employing common-collector resisitive feedback in 0.35 um bipolar SiGe technology - Radwan, Ahmed; Weigel, Robert; Kissinger, Dietmar (IEEE MTT-S International Microwave Symposium, 2014)
elib2cris::1512001600,gharib2014

A 70 to 90 GHz High-Linearity Multi-Band Quadrature Receiver in 0.35 μm SiGe Technology - Nasr, Ismail; Lämmle, Benjamin; Aufinger, Klaus; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE Transactions on Microwave Theory and Techniques, 2013)
An integrated frequency agile quadrature E-band receiver is presented in this paper. The complete receiver is realized in a commercial 0.35μm SiGe:C technology with an ft=fmax of 170/250GHz. The receiver covers the two point to point communication bands from 71 to 76 GHz and 81 to 86 GHz and the automotive radar band at 77 GHz. A wide tuning range modified Colpitts oscillator provides an LO tuning range > 30%. A two stage constant phase RC polyphase network is implemented to provide wide-band quadrature (IQ) LO signals. The measured phase imbalance of the network stays below 8 over the receiver’s frequency range. In addition the chip includes a wide-band LNA, Wilkinson power divider, down conversion mixers and frequency prescaler. Each of the chip’s receiver I/Q paths shows a measured conversion gain above 19 dB and an input referred 1 dB compression point of -22 dBm. The receiver’s measured noise figure stays below 11 dB over the complete frequency range. Furthermore, the receiver has a measured IF bandwidth of 6 GHz. The complete chip including prescaler draws a current of 230mA from a 3.3V supply, and consumes a chip area of 1628μm x 1528 μm.
elib2cris::1512001600,nasr2013b

A 77-GHz Down-Conversion Mixer Architecture with Built-In Test Capability in SiGe Technology - Kissinger, Dietmar; Knapp, Herbert; Maurer, Linus; Weigel, Robert (Bipolar/BiCMOS Circuits and Technology Meeting, 2010)
A 77-GHz double-balanced mixer in a 200 GHz ft silicon-germanium technology is presented. The proposed mixer architecture is capable of simultaneous direct up- and down-conversion of two separate input signals without additional power consumption. An up-converted low-frequency test signal is coupled back into the receiver RF input path to enable a built-in functionality test of the down-conversion path of the mixer. The circuit exhibits a conversion gain of 20 dB and draws 22mA from a 3.3V supply. The fabricated chip occupies an area of 1028 × 1128μm2.
elib2cris::1512001600,kissinger2010d
Keywords: Frequency measurement; Impedance matching; Mixers; Power generation; Radio frequency; Receivers; Silicon germanium

A 77-GHz FMCW Radar Transceiver sourced through a 19 GHz SiGe Colpitts Oscillator - Starzer, Florian; Forstner, Hans-Peter; Wagner, Christoph; Fischer, A.; Jäger, Herbert; Kissinger, Dietmar; Stelzer, Andreas (Asia Pacific Microwave Conference, 2009)
elib2cris::1512001600,starzer2009

A Broadband 10-95 GHz Variable Gain Ampliﬁer in a 130 nm BiCMOS Technology - Bauch, Andreas; Dietz, Marco; Weigel, Robert; Hagelauer, Amelie Marietta; Kissinger, Dietmar (European Microwave Integrated Circuits Conference, 2017)

A broadband 1.33 THz GBP 120-mW common-collector feedback amplifier in SiGe technology - Radwan, Ahmed; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE Bipolar/BiCMOS Technology and Devices Meeting, 2012)
elib2cris::1512001600,gharib2012

A broadband 24 GHz bandwidth 54 dB gain 180-mW amplifier employing common-collector combinded with capacitive controlled cross-coupled feedback in 0.35 um SiGe technology - Radwan, Ahmed; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE Bipolar/BiCMOS Circuits and Technology Meeting, 2013)
elib2cris::1512001600,gharib2013

A Broadband 3-29 GHz Reflectometer with a Frequency Compensated Multilayer Sixport Structure - Trenz, Florian; Hofmann, Maximilian; Weigel, Robert; Kissinger, Dietmar (2015 European Microwave Week, 2015)
In this paper, a planar broadband sixport reflectometer structure is presented. A frequency range from 3 to 29 GHz could be achieved by merging broadband components into a single multilayer pcb stackup with an area of 66x55 mm2 . The reflectometric architecture used herein allows a frequency independent q-point configuration of the sixport by implementing microstrip linelength compensation. Broadband matching of around -10 dB could be reached at all ports in a frequency range from 1 to 30 GHz. Acceptable coupling from DUT port to measurement output could be reached in a range from 2 to 29 GHz. Frequency compensation of the structure and an optimal q-point constellation of 120-120-120 have been verified by measurement. Due to its broadband functionality, compactness and cost efficiency, the proposed system is suitable for a wide range of microwave measurement applications.
elib2cris::1512001600,trenz2015
Keywords: Reflectometry; sixport; Microwave circuits; broadband

A Cascadable Integrated Bistatic Six-port Transceiver at 60 GHz in a 130-nm BiCMOS Technology for SIMO-Radar Applications - Völkel, Matthias; Pechmann, Stefan; Hussein, Eissa Mohamed; Kissinger, Dietmar; Weigel, Robert; Hagelauer, Amelie Marietta (APMC, 2019)
In this paper a 60 GHz cascadable bistatic integrated interferometric transceiver for SIMO radar applications is presented. The integrated transceiver has been designed in a 0.13μm SiGe BiCMOS technology (SG13G2) from the institute innovations for high performance microelectronics (IHP). The System includes a 15 GHz buffer stage, a low noise amplifier, a passive interferometric six-port structure, several detectors and amplifiers as well as a digital interface. The chip has a size of 2.75mm x 1.15mm and a maximum power consumption of 525mW from a 3.3V power supply. The 15 GHz frequency input is multiplied to reach a 60 GHz signal at a minimum input power of -40 dBm. The chip delivers a maximum output power of 10.2 dBm. A digital interface adjusts the output power between -22 and 10,2 dBm at an output frequency of 60 GHz. The reference input power of the six-port and the RF input power could be adjusted in a range of 13.2 dB. The maximum P1dB is at -24.1 dBm. The measured power detector sensitivity is 7090 V/W. The standard deviation of the phase measurement is 0.025 rad.<br
Keywords: bistatic; industrial radar; integrated transceiver; interferometric radar; millimeter wave circuits; SIMO Radar; MMIC; SiGe BiCMOS; six-port; system-on-chip (SoC)

A clock synchronization for M-sequence-based ultra-wideband systems - Hamouda, Mohammed; Guarin Aristizabal, Gustavo Adolfo; Gardill, Markus; Lämmle, Benjamin; Weigel, Robert; Kissinger, Dietmar; Ußmüller, Thomas (IEEE Transactions on Microwave Theory and Techniques, 2014)
elib2cris::1512001600,hamouda2014c

A Compact Back-Plaster Sensor Node for Dementia and Alzheimer Patient Care - Schwarzmeier, Andre; Besser, J.; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (2014 IEEE Sensors Applications Symposium (SAS 2014), 2014)
Abstract— This paper presents a compact and highly integrated back-plaster sensor node equipped with seamless localization (in-door and out-door) using assisted GPS and bluetooth localization, activity classification and fall detection as well an GSM module providing a GPRS connection to a server infrastructure for supporting dementia and Alzheimer patients within their daily life. The innovative and durable design as a hermetic rubber-sealed, waterproof and sanitizable back-plaster ensures optimum wearing comfort for the patient as well as reliable fall-detection. In addition with an internet server infrastructure the described plaster sensor node allows to inform relatives or professional care staff in case of an emergency and help to enhance the quality of life by increasing the sense of feeling secure.
elib2cris::1512001600,schwarzmeier2014
Keywords: Index Terms— remote health monitoring; medical information system; fall-detection; localization; sensor processing; data fusion

A compact medical platform for mobile sensor fusion and data communication - Agethen, Roman; Reuter, Lukas Michael; Lurz, Fabian; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE International Workshop on Medical Measurements and Applications (MeMeA), 2011)
elib2cris::1512001600,agethen2011

A Differential 77-GHz Receiver with Current Re-Use Low-Noise Amplifier in SiGe Technology - Kissinger, Dietmar; Forstner, Hans-Peter; Jäger, Herbert; Maurer, Linus; Weigel, Robert (In: IEEE Topical Meeting on Silicon Monolithic Intergated Circuits in RF Systems (SiRF), 2010)
elib2cris::1512001600,kissinger2010
Keywords: Automotive engineering; Circuits; Gain; Germanium silicon alloys; Heterojunction bipolar transistors; Low-noise amplifiers; Manufacturing; Noise figure; radar; Silicon germanium

A Digital Adjustable Fully Integrated Bistatic Interferometric Radar Transceiver at 60 GHz in a 130 nm BiCMOS Technology - Völkel, Matthias; Dietz, Marco; Hagelauer, Amelie Marietta; Hussein, E. M.; Kissinger, Dietmar; Weigel, Robert (EUMW, 2019)
In this paper a 60 GHz monolithic bistatic interferometric radar transceiver for high precision measuring is presented. The integrated transceiver has been designed using a 0.13μm SiGe BiCMOS process from IHP (SG13G2) and includes a LNA, a passive six-port structure, detectors, multiplier, multiplexer, power amplifier and a digital interface. The chip has a size of 2330μm x 1360μm and a maximum power consumption of 533mW from a 3.3V power supply. The circuit provides two frequency inputs of 7.5 and 15GHz and multiplies them up to 60 GHz at a minimum input power of -20 dBm. The chip delivers a maximum output power of 9dBm at 61 GHz. The input path is selectable and the output power is adjustable by a digital interface between -23 and 9dBm at 60 GHz. Also the reference input power of the six-port and the RF input power can be adjusted in a range of 13.2 dB. The minimum input referred P1dB is -24.1 dBm. With a multiplexer, the receiver reference can be separated from the transmitter, which allows the use of both independently from each other. The serial interface is realized in 0.13μm CMOS logic and consists of a 20 bit shift register, decoder and an analog interface.<br
Keywords: bistatic radar; digital adjustable; industrial radar; integrated transceiver; interferometric radar; millimeter wave circuits; SiGe BiCMOS; six-port

A Fall Detection and Activity Monitoring Algorithm for a Tele-Care System Supporting Dementia and Alzheimer Patients - Schwarzmeier, Andre; Roth, Nils; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (BMT 2014 - 48. Jahrestagung der DGBMT, 2014)
Dementia and Alzheimer patients who show a “wandering” behaviour combined with excessive activity and unsteady gait are exposed to a particular risk of dangerous falls. Fast and efficient help in case of such an emergency could be provided by a tele-care system comprising a mobile back-plaster as an on-body sensor node that is equipped with sen-sors which not only capture activity and movement data from the patient but also enable indoor and outdoor localiza-tion. This node is linked to an internet server infrastructure including a back-end software. In order to enhance the care quality reliable algorithms for activity monitoring and fall detection are needed.
elib2cris::1512001600,schwarzmeier2014a

A Fully Differential Low-Power High-Linearity 77-GHz SiGe Receiver Frontend for Automotive Radar Systems - Kissinger, Dietmar; Weigel, Robert (Wireless and Microwave Technology Conference, 2009)
elib2cris::1512001600,kissinger2009

A fully integrated 120-GHz six-port receiver front-end in a 130-nm SiGe BiCMOS technology - Lämmle, Benjamin; Schmalz, Klaus; Borngraeber, J.; Scheytt, Christoph; Weigel, Robert; Kölpin, Alexander; Kissinger, Dietmar (2013 IEEE 13th Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems, 2013)
A fully integrated six-port receiver front-end at 120 GHz center frequency including a low-noise-amplifier, a passive six-port network, a VCO, and four direct converters is presented in this publication. The overall architecture of the designed six-port receiver is analyzed and fundamental theory of the receiver given. The design of the six-port building blocks is described and measurement results are presented. All circuits have been fabricated in a 0.13μm 300-GHz fT SiGe BiCMOS technology. The fully integrated receiver consumes 85.9 rnA from a 3.3-V supply and occupies an area of 1.03mm2. The receiver includes a VCO with a center frequency of 117.15 GHz, a tuning range of 2.7 GHz, and a phase noise of -86 dBc/Hz at 1 MHz offset. The LNA shows a gain of 12 dB, a 3-dB bandwidth of 30 GHz at a power consumption of 9.2 rnA. The six-port core has a conversion gain of 3.6 dB, a P1dB of -12 dBm, and a power consumption of 28 rnA. The overall receiver shows a conversion gain of 2.4 dB at 120 GHz and P1dB of -17 dBm.
elib2cris::1512001600,laemmle2013

A High-Gain High-Linearity Tapered Distributed Amplifier for Ultra-Wideband-Applications Using a Low Cost SiGe BiCMOS Technology - Sewiolo, Benjamin; Kissinger, Dietmar; Fischer, Georg; Weigel, Robert (IEEE Wireless and Microwave Technology Conference, 2009)
elib2cris::1512001600,sewiolo2009c

A High-Linearity Broadband 55-77 GHz Differential Low-Noise Amplifier with 20 dB Gain in SiGe Technology - Kissinger, Dietmar; Aufinger, Klaus; Meister, Thomas; Maurer, Linus; Weigel, Robert (Asia-Pacific Microwave Conference (APMC 2010), 2010)
This paper presents a broadband differential current re-use low-noise amplifier with 30% fractional bandwidth at a center frequency of 66 GHz. The circuit has been manufactured in an advanced SiGe:C HBT technology with ft/fmax = 220/285 GHz. The amplifier is unconditionally stable and achieves a maximum differential gain of 19.7 dB while operating over a 3-dB bandwidth of 22 GHz. At the upper corner frequency of 77 GHz the amplifier exhibits a noise figure of 5.8 dB and linearity measurements show a 1-dB output referred compression point above +3 dBm. The circuit consumes 40 mW from a 3.3 V supply and occupies a chip area of 728 × 728 μm2 including bond pads.
elib2cris::1512001600,kissinger2010e
Keywords: Broadband communication; CMOS integrated circuits; Frequency measurement; Gain; Noise; Silicon; Silicon germanium

A Highly Sensitive Glucose Biosensor Based on a Microstrip Ring Resonator - Schwerthöffer, Udo; Weigel, Robert; Kissinger, Dietmar (2013 IEEE MTT-S International Microwave Workshop Series on RF and Wireless Technologies for Biomedical and Healthcare Applications, 2013)
elib2cris::1512001600,schwerthoeffer2013a

A Low-Power 120-GHz Integrated Sixport Receiver Front-End with Digital Adjustable Gain in a 130-nm BiCMOS Technology - Völkel, Matthias; Hirsch, Hartmut; Dietz, Marco; Weigel, Robert; Hagelauer, Amelie Marietta; Kissinger, Dietmar (IEEE Bipolar/BiCMOS Circuits and Technology Meeting, 2017)
In this paper a 120GHz monolithic low-power sixport receiver front-end including two variable gain amplifiers, a passive sixport network, four detectors and a digital serial interface (SPI) is presented. The measurement principle is based on the additive superposition of two incident millimeter-wave signals, whereas the superposition must be fulfilled under special conditions. After power detection, the quadrature components can be extracted. The proposed measurement system is well suited for industrial radar applications, as well as for biomedical applications and it is further more well suited for communication systems. The receiver has been designed using a 0.13μm SiGe BiCMOS process from IHP (SG13G2). The whole integrated circuit has a size of 1560μm x 900μm and only consumes 102.3mW from a 3.3V supply. The receiver exhibits a 1 dB compression point of -13dBm at the center frequency. The bandwidth is 15.5 GHz and covers the lower part of the D-Band. The gain of the input amplifier can be adjusted from 3 to 16 dB by a digital interface. The maximum power consumption of the VGA is 46.2m
Keywords: industrial radar; communication receiver; interferometer; phase measurement; sixport; low power; SiGe BiCMOS; millimeter-wave

A Low-Power 60-GHz Integrated Sixport Receiver Front-End in a 130-nm BiCMOS Technology - Völkel, Matthias; Dietz, Marco; Weigel, Robert; Hagelauer, Amelie Marietta; Kissinger, Dietmar (European Microwave Integrated Circuits Conference, 2017)
Abstract—In this paper a 60 GHz monolithic low-power sixport receiver front-end for high precision industrial radar systems is presented. The measurement principle is based on the passive superposition and power detection of two incident millimeterwave signals. The integrated receiver has been designed using a 0.13μm SiGe BiCMOS process from IHP (SG13G2) and includes a low noise amplifier (LNA), the passive sixport structure and four detectors. The signal processing in the baseband is done with an ADC-board designed with components from Texas Instruments and a Cyclone IV FPGA board. The integrated receiver circuit has a size of 1320μm x 950μm and a low power consumption of 73mW from a 3.3V supply.
Keywords: industrial radar; interferometer; phase measurement; sixport; low power; SiGe BiCMOS

A Low-Power Embedded Communication Platform for Medical Applications - Schwarzmeier, Andre; Reuter, Lukas Michael; Mena-Carrillo, Juan; Weber, Werner; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (46th annual conference of the German Society for Biomedical Engineering, 2012)
Introduction This paper presents a scalable, flexible and energy efficient embedded communication platform for seamless data transfer of medical sensor signals from the sensor acquisition point to a medical service centre. The presented platform can be used as an assistance system for improved medical support and care of patients and lifestyle users by providing vital parameter data to the service centre for a variety of individual assistance services. Methods The presented hardware platform is comprised of two functional blocks. A sensor platform has been implemented containing a medical device controller for collection of the data of various medical sensors connected via an analog front end or by an integrated Bluetooth transceiver module. Furthermore, a communication module including an A-GPS receiver enables GSM and UMTS data and voice connections to a central infrastructure and provides positioning data of the patient current location. The software protocol stack for the sensor data transmission is kept flexible in order to allow different communication standards. Special emphasis has been put on the energy management concept to optimize the battery life time and increase patient acceptance. Results The modular hardware and software co-design allows the connection of a wide range of different medical sensors, adjusted to the patient needs and specific use case. The use of data reduction and pre-processing techniques allows a reduction of the amount of data transferred to the infrastructure. Additionally, the centralized aggregation of sensor data enables short transmission times. This, in conjunction with an application specific energy management concept, leads to an increased battery life time. Conclusion The presented platform allows the collection of vital parameters from a variety of medical sensors for personal assistance of patients and elderly people. This concept allows new possibilities in diagnosis and treatment with the goal of an increased quality of life through the extension of independent at-home living periods.
elib2cris::1512001600,schwarzmeier2012
Keywords: Medical; Platform; Energy; Budget

A Low-Power Fall Detection and Activity Monitoring System for Nursing Facilities and Hospitals - Schwarzmeier, Andre; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (IEEE Topical Conference on Bio-medical Wireless Technologies, Networks, and Sensing Systems (BioWireleSS2014), 2014)
Abstract— This paper presents a fall detection and activity monitoring system comprised of a server software for data management, multiple UHF RFID readers and an energy efficient, small and lightweight semi-passive UHF RFID sensor tag. The system is able to gather activity and indoor localization data of several persons wearing just one sensor tag, making it particularly suitable for the use in nursing facilities or hospitals. The implemented fall detection alerts nursing staff in case of a detected fall and allows quick intervention in case of an emergency.
elib2cris::1512001600,schwarzmeier2013
Keywords: Index Terms— semi active UHF RFID; remote fall monitoring; sensor tag; localization; Ambient Assisted Living (AAL); sensor processing

A Low-Power Wideband D-Band LNA in a 130 nm BiCMOS Technology for Imaging Applications - Aguilar Mendoza, Erick; Hagelauer, Amelie Marietta; Kissinger, Dietmar; Weigel, Robert (Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems, 2018)
A Low-power D-Band Low Noise Amplifier (LNA) manufactured in a recent 130 nm SiGe BiCMOS process for imaging applications is presented. The architecture consists of an optimized 3-stage cascode amplifier which achieves a maximum gain of 32.8 dB and a gain>20 dB in the frequency range from 121 to 161 GHz with a DC power consumption of 39.6 mW. The simulated noise figure varies from 6 to 9.7 dB within the range 130 to 140 GHz. To the best of the author’s knowledge, the presented work exhibits the highest gain-bandwidth product with the lowest power consumption for a D-Band amplifier in a 130 nm SiGe technology.
Keywords: D-Band; Imaging; Radiometrie; LNA; SiGe; mm-wave

A Microstrip Resonant Biosensor for Aqueous Glucose Detection in Microfluidic Medical Applications - Schwerthöffer, Udo; Warter, Christoph; Weigel, Robert; Kissinger, Dietmar (2014 IEEE Topical Conference on Bio-medical Wireless Technologies, Networks, and Sensing Systems (BioWireleSS2014), 2013)
elib2cris::1512001600,schwerthoeffer2013b

A microwave permittivity sensing system based on a hybrid heterodyne reflectometer circuit - Nehring, Johannes; Schütz, Martin; Weigel, Robert; Kissinger, Dietmar (Microwave Conference (EuMC), 2014 44th European, 2014)

A Microwave Sensing System for Aqueous Concentration Measurements based on a Microwave Reflectometer - Hofmann, Maximilian; Trenz, Florian; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (2012 IEEE MTT-S International Microwave Symposium Digest (MTT), 2012)
This paper presents a novel parameterized Debye relaxation model for aqueous glucose solutions up to 40 GHz. The influence on all Debye relaxation parameters is given by three equations. A compact microwave demon- strator for concentration measurements, consisting of two directional couplers, a voltage controlled oscillator (VCO), a six-port-junction, power detectors and a signal processing board is introduced. A hybrid calibration procedure for the reflectometer based approach is applied, based on a linear five standard calibration and a three standard error-box model, respectively.
elib2cris::1512001600,hofmann2012c
Keywords: Diabetes; Electromagnetic reflection; Relaxation methods

A Microwave VNA for Biomedical In-line Concentration Measurements - Hofmann, Maximilian; Bauch, Andreas; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (BioWireless Conference, 2013)
This paper presents a microwave (MW) test-set designed for biomedical in-line concentration measurements. The demonstrator consists of a commercial voltage controlled oscillator (VCO) with an output power of up to +12.0 dBm, feeding an asymmetric 4 way power divider. A fraction of 0 dBm of the VCO output is driving three I-Q mixers, which realizes a homodyne vector network analyzer. Dual directional couplers were investigated concerning the application for concentration measurements. A wiggly line coupler was separately fabricated and measured as well as implemented in the demonstrator. The entire system is fabricated, calibrated and subsequently characterized with a transmission based permittivity sensor.
elib2cris::1512001600,hofmann2013a

A millimeter-wave FMCW radar system simulator for automotive applications including nonlinear component models - Dudek, Manuel; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (European Radar Conference (EuRAD), 2011)
A fully differential millimeter wave frequency modulated continuous wave (FMCW) radar architecture is built up in Agilent's RF design and system simulation environment ADS® to investigate the influence of RF impairments on system level on the target signal. To take also the surroundings of the automotive scenario into account a 3D ray tracing channel simulator is coupled in a Matlab® co-simulation providing realistic data of the traffic situation. Therefore investigations on the performance of the radar frontend in an automotive long range radar (LRR) application are enabled, the functionality of the circuitry can be verified and components designed in the most beneficial way, so that the best performance is achieved with the available resources. For nonlinear behavior the frontend components are parameterized according to recently published values for 77GHz SiGe circuits. The functionality of the complete simulation environment is demonstrated by calculating a typical traffic situation.
elib2cris::1512001600,dudek2011c

A mobile microcontroller platform for sensor fusion and communication - Reuter, Lukas Michael; Agethen, Roman; Lurz, Fabian; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (Embedded World Conference, 2012)
elib2cris::1512001600,reuter2012

A Multiband 2-Port Vector Network Analyzer based on Six-Port Junctions for Biomedical Measurement Applications between 6 GHz and 33 GHz - Linz, Sarah; Hofmann, Maximilian; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (2013 IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications (APWC), 2013)
Concentration measurements of dissolved substances in fluids are of great interest for biomedical as well as industrial applications. In this work a multiband vector network analyzer is presented that is capable of determining phase variations due to changes in the concentration. A topology comprising two Six-Port networks optimized for the frequencies 6.6 GHz, 19.7GHz and 32.4GHz has been implemented. Measurement results show a characteristic change of the phase when increasing the glucose concentration in binary aqueous solutions.
elib2cris::1512001600,linz2013
Keywords: Six-Port; multiband

A Multiband 2-Port VNA for Biomedical Applications based on two Six-Port-Junctions - Hofmann, Maximilian; Linz, Sarah; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (2013 IEEE MTT-S International Microwave Symposium Digest (IMS), 2013)
This paper presents a triple band two port vector network analyzer (VNA) consisting of two six-port-junctions for biomedical concentration measurements. The microwave sensing system is designed to operate with a 10% bandwidth around 6.6 GHz, 19.7 GHz and 32.4 GHz. An embedded coplanar permit- tivity sensor will be applied for measurements of aqueous glucose solutions. The entire microwave sensing system is designed, fab- ricated and characterized with different glucose concentrations in binary solutions.
elib2cris::1512001600,hofmann2013c

An 8-32GHz Frequency Synthesizer based on a Wideband VCO Array with Bandwidth Extension Stage - Nehring, Johannes; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (German Microwave Conference (Gemic), 2014)
This paper proposes a wideband signal source covering a bandwidth of two octaves from 8 GHz to 32 GHz. The system is based on an array of three wideband voltage controlled oscillators (VCOs) for octave wide frequency syn- thesis and a post-synthesis stage which extends the bandwidth by another octave. The circuits were fabricated in a 0.35 μm SiGe bipolar technology with an ft/fmax= 170/250GHz. The VCO tuning ranges are 28.9 %, 26.2 % and 24.7 % respectively. The average output power was measured to be −3.5 dBm. The single-sideband phase noise at 1 MHz offset has an average value of −100 dBc/Hz over the entire bandwidth of two octaves. The system blocks VCO array, bandwidth extension and output buffer consume a power of 175 mW, 277 mW and 150 mW.
elib2cris::1512001600,nehring2014a

An 8-32 GHz frequency synthesizer based on a wideband VCO array with bandwidth extension stage - Nehring, Johannes; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (8th German Microwave Conference, GeMiC 2014, 2019)
This paper proposes a wideband signal source covering a bandwidth of two octaves from 8 GHz to 32 GHz. The system is based on an array of three wideband voltage controlled oscillators (VCOs) for octave wide frequency synthesis and a post-synthesis stage which extends the bandwidth by another octave. The circuits were fabricated in a 0.35 µm SiGe bipolar technology with an ft/fmax = 170/250 GHz. The VCO tuning ranges are 28.9 %, 26.2 % and 24.7 % respectively. The average output power was measured to be −3.5 dBm. The single-sideband phase noise at 1 MHz offset has an average value of −100 dBc/Hz over the entire bandwidth of two octaves. The system blocks VCO array, bandwidth extension and output buffer consume a power of 175 mW, 277 mW and 150 mW.
CRIS-Team Scopus Importer:2021-04-20
Keywords: VCO; Voltage controlled oscillator; Wideband frequency synthesis

An Advanced Millimeter-Wave FMCW-Radar System Simulation Environment for the Automotive Sector - Dudek, Manuel; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (12. GMM/ITG-Fachtagung ANALOG, 2011)
In this paper a millimeter-wave radar system simulation environment for frequency-modulated continuous-wave radar using a 3D ray tracing channel simulator is presented. Therefore we use Agilent’s RF design environment ADS® for system simulation and calculate the channel impulse response based on the data received from a 3D ray tracer in a Matlab® co-simulation. To reduce computing time the whole signal flow is processed in a complex baseband representation and scattering center models are used as substitute for complex polygon targets as further improvement. Nevertheless all effects occurring at harmonic bands due to nonlinearities in the transmitter and receiver circuits are well reflected in the simulation. A typical road scenario is simulated and the results show the capabilities of the simulation approach in terms of speed and accuracy.
elib2cris::1512001600,dudek2011e

Analysis of a built-in test architecture for direct-conversion SiGe millimeter-wave receiver frontends - Kissinger, Dietmar; Agethen, Roman; Weigel, Robert (IEEE Instrumentation and Measurement Technology Conference, 2010)
elib2cris::1512001600,kissinger2010c

An integrated 125 GHz sensor with read-out circuit for permittivity measurement of liquids - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Weigel, Robert; Kissinger, Dietmar (IEEE MTT-S International Microwave Symposium, 2012)
elib2cris::1512001600,laemmle2012a

An online telemetering system for mobile health parameter monitoring and medical assistance - Agethen, Roman; Lurz, Fabian; Schwarzmeier, Andre; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (Internation Conference on Sensing Technology, 2011)
elib2cris::1512001600,agethen2011b

A novel approach to non-invasive blood glucose measurement based on RF transmission - Hofmann, Maximilian; Fersch, Thomas; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (IEEE International Workshop on Medical Measurements and Applications, 2011)
A new approach to non-invasive blood parameter measuring is presented, which consists of two matched antennas for transmission based two port measurements. The current situation of patients suffering from diabetes mellitus and their need for novel blood sugar level measuring techniques is presented. Dielectric properties of body tissues are reviewed and their influence on transmission properties are estimated for plane wave propagation. A covered patch antenna and substrate integrated waveguide slot antenna has been designed, measured and compromised for glucose-concentration measurements. Further, several test locations are discussed with respect to an accurate measurement. The introduced antennas were optimized and fabricated with respect to the dielectric and mounting properties of human tissues.
elib2cris::1512001600,hofmann2011b

Antenna and Package Design for 61 GHz and 122 GHz Radar Sensors in Embedded Wafer-Level Ball Grid Array Technology - Frank, Martin; Reißland, Torsten; Lurz, Fabian; Völkel, Matthias; Lambrecht, Franziska; Kiefl, Stefan; Ghesquiere, Pol; Ng, Herman; Kissinger, Dietmar; Weigel, Robert; Kölpin, Alexander (IEEE Transactions on Microwave Theory and Techniques, 2018)

A Permittivity Sensitive Phase-Locked Loop Based on a Silicon-Integrated Capacitive Sensor for Microwave Biosensing Applications - Nehring, Johannes; Bartels, Melanie; Weigel, Robert; Kissinger, Dietmar (IEEE Topical Conference on Biomedical Wireless Technologies, Networks & Sensing Systems, 2015)
elib2cris::1512001600,nehring2015

A Silicon Integrated Microwave Vector Network Analyzer for Biomedical Sensor Read-Out Applications - Nehring, Johannes; Nasr, Ismail; Borutta, Karl; Weigel, Robert; Kissinger, Dietmar (IEEE MTT-S International Microwave Symposium (IMS), 2014)
This paper proposes an integrated reflectometer for biomedical sensor read-out applications using a low-cost silicon- germanium technology. The heterodyne reflectometer consists of two integrated cross-coupled oscillators, a set of two directional couplers as well as Gilbert-Cell downconversion mixers. A dual phase-locked-loop architecture guarantees the phase lock of both on-chip signal sources to an external reference oscillator. An OSM-calibration was applied to the reflectometer and measure- ments of the complex reflection coefficient of an arbitrary device under test (DUT) showed excellent agreement with the results of a commercial vector network analyzer. As a proof of concept for sensor read-out, five solutions with different mixture ratios were characterized with a dielectric probe connected to the reflectometer.
elib2cris::1512001600,nehring2014

A Single-Chip 15-32 GHz Signal Source in SiGe Bipolar Technology - Nehring, Johannes; Nasr, Ismail; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (European Microwave Integrated Circuits Conference (EuMIC), 2013)
This paper presents a single-chip octave-bandwidth signal source covering a frequency band from 15GHz to 32GHz. The circuit was fabricated in a 0.35 μm SiGe bipolar technology with an ft/fmax = 170/250GHz. An array of four crosscoupled voltage controlled oscillators with subsequent frequency ranges is implemented. The oscillator cores only draw 13mA from a 3.3V supply. Another 13mA is drawn by following buffer stages. A 4-to-1 multiplexing amplifier acts as a combiner providing the octave-wide bandwidth at a single differential output. The output power was measured to be between -2.5 dBm and 0.7 dBm. The signal source provides a good phase noise performance of -105 dBc/Hz at 15GHz and -96.8 dBc/Hz at 30GHz at an offset of 100MHz from the carrier frequencies. The overall circuit consumes a total power of 205mW and occupies a chip area of 1128 μm x 1028 μm.
elib2cris::1512001600,nehring2013
Keywords: VCO; signal source; wideband; microwave; octave-wide bandwidth

Asynchronous Subthreshold CMOS Event Detector for Wireless BAN Sensor Nodes - Grimminger, Florian; Kowalczyk, G.; Unterassinger, H.; Schwarzmeier, Andre; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE BioWireleSS, 2013)
This work presents the implementation of an asynchronous event detector circuit by applying subthreshold standard cells. The presented circuit operates in an on-chip power management unit (PMU) of a wireless sensor node. Such an application demands an ultra-low power architecture for an increased overall lifetime of the sensor node. The asynchronous circuit architecture and its subthreshold logic implementation both significantly reduce the leakage power dissipation by factor three. The presented event detector is realized in a 130 nm CMOS process with regular transistors operating from a 200 mV supply voltage.
elib2cris::1512001600,grimminger2013
Keywords: Subthreshold; Asynchronouse; Event detector; Wireless sensor node

A Universal Method for the Design and Synthesis of Wideband Directional Couplers using Non-Uniform Coupled Transmission Lines - Nehring, Johannes; Hofmann, Maximilian; Münker, Christian; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (IEEE European Microwave Conference, 2012)
In this paper a complete procedure for the design, synthesis and construction of wideband directional couplers is presented. Cascading multiple quarter-wavelength line segments leads to an increase of coupling bandwidth up to 180% but also results in discontinuities of geometry and thus in strong reflec- tions. Furthermore, the isolation is diminished. To avoid these effects a design technique for the generation of continous, non-uniform geometries is analyzed and implemented. Two methods for the coupler synthesis are proposed and compared. One is an approximational approach and uses two sets of equations. The other uses accurate 2D field simulation of the propagating modes and is universally applicable to any kind of coupled transmission lines. The completely synthesized couplers are simulated in CST Microwave Studio and achieve very good results for coupling, isolation and return loss. A nominal -10dB wideband coupler at a center frequency of 15GHz and a nominal bandwidth of 164% is built in a multilayer stackup. Good agreement between measurement and simulation results is observed.
elib2cris::1512001600,nehring2012
Keywords: wideband directional coupler; wideband; coupler; non-uniform

A Versatile 10–80-Gb/s PRBS-Based Broadband Transmitter With Arbitrary 20–60-GHz Spectrum Shifting - Gharib, Ahmed; Weigel, Robert; Kissinger, Dietmar (IEEE Transactions on Microwave Theory and Techniques, 2016)

A Versatile Built-In Test Architecture for Integrated Millimeter-Wave Radar Receiver Front-Ends - Kissinger, Dietmar; Agethen, Roman; Weigel, Robert (IEEE International Instrumentation and Measurement Technology Conference (I2MTC), 2012, 2012)
This paper presents a versatile direct built-in test architecture for integrated radar receiver front-ends. It is used for determination of the gain and noise figure of a direct down-conversion receiver. The general test structure is introduced and a detailed analysis of different approaches for the test signal injection and calibration are given.
elib2cris::1512001600,kissinger2012b
Keywords: built-in self test; millimetre wave radar; radar receivers; built-in test architecture; direct down-conversion receiver; integrated millimeter-wave radar receiver front-end; millimeter wave; Noise measurement

A Versatile System Simulation Environment for Millimeter-Wave Phased-Array FMCW-Radar Sensors for Automotive Applications - Dudek, Manuel; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (Asia-Pacific Microwave Conference (APMC), 2011)
In this contribution a versatile system simulation environment for radar sensors being developed to operate in the automotive area is introduced. It combines a frontend simulation engine that is coupled in a co-simulation with a 3D ray-tracing tool to take the effects of the automotive radar channel into account, thus providing accurate and reliable results concerning the behavior of the implemented circuits in certain traffic situations. With respect to the latest developments in automotive radar, i.e. the transition from former comfort systems to current systems including an increased number of safety functions, the system simulation environment has been extended to support investigations on the phased-array radar principle. Applying this technique in the automotive area promises advantages in target detection in the vehicles vicinity by the means of increased hardware requirements, resulting in radar systems that are by far more difficult to design due to the number of side-effects that have to be additionally considered during the development process. To demonstrate the capability of this advanced simulation approach a typical traffic scenario is calculated showing not only the advantages of phased-array radar for the automotive field but also the performance of the simulation environment built up.
elib2cris::1512001600,dudek2011f

A Wideband Scalar Network Analyzer for Biomedical Dehydration Measurements - Hofmann, Maximilian; Nehring, Johannes; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (IEEE Engineering in Medicine and Biology Conference (EMBC), 2013)
This paper presents a wideband microwave ap- proach towards biomedical dehydration monitoring. The intro- duced concept is verified via invasive measurements on several blood samples. A microwave measurement circuit, based of a two-port scalar vector network analyzer is presented. The circuit operates between 5GHz and 20GHz using a planar permittivity sensor. Measurements of all subcomponents are shown together with measurements of a Water-NaCl-Glycerol solution.
elib2cris::1512001600,hofmann2013d

A wide tuning range high output power 56-74 GHz VCO with on-chip transformer load in SiGe technology - Nasr, Ismail; Lämmle, Benjamin; Knapp, Herbert; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE Topical Meeting Silicon Monolithic Integrated Circuits in RF Systems Digest, 2012)
This paper presents a wide tuning range modified Colpitts VCO with high output power. The circuit was fabricated using a lowcost SiGe technology with an ft/fmax of 170/250 GHz. The VCO can be tuned between 56.4 and 73.8 GHz having a tuning range of approx. 27%. The maximum measured output power is +9.4 dBm, and the output power remains above +7.0 dBm over the entire tuning range. The VCO has a minimum phase noise of -95 dBc/Hz, which stays below -88 dBc/Hz over the entire tuning range. On-chip frequency dividers were used to enable easier measurement. A single transformer was designed and used simultaneously for output matching of the VCO and as an output balun. The overall chip draws 112 mA from a 3.3 V supply, where the VCO draws 45 mA of the total current.
elib2cris::1512001600,nasr2012
Keywords: VCO; Transformer; Frequency Dividers; Colpitts; FMCW

Biowireless 2014 (feature column) - Kissinger, Dietmar (IEEE Microwave Magazine, 2013)
elib2cris::1512001600,kissinger2013a

Broadband Circuit Techniques for Multi-Terahertz Gain-Bandwidth-Product Low-Power Applications - Radwan, Ahmed; Weigel, Robert; Kissinger, Dietmar (IEEE Transactions on Microwave Theory and Techniques, 2015)
In this paper, two proposed bandwidth (BW) extension techniques are discussed and analytically analyzed. The capabilities of the proposed feedback techniques are demonstrated with two design examples of different circuitry, supported by simulation and measurement results. The first design example is a broadband low-power active balun, employing one of the presented feedback techniques. It is capable of operating with a gain of 2.2 dB and BW of more than 70 GHz. The amplitude imbalance is less than 2.4 dB, while the phase imbalance is below 7 ° up to 60 GHz and 14 ° up to 70 GHz, consuming a low-power of 29.7 mW. The second design example is a differential three-stage amplifier, incorporating the two techniques, where their combined performance achieves a gain of 54 dB and a 3-dB BW of 25 GHz, resulting in a gain-BW product (GBP) of 12.5 THz, with a power consumption of 180 mW from a 3.3-V supply. The chips are fabricated in a 0.35- μm SiGe:C bipolar technology with a ft/ fmax of 200/250 GHz.
elib2cris::1512001600,gharib2015

Broadband Millimeter-Wave Receiver Front-Ends in Silicon-Germanium Technology for Multi-Band Communication Systems - Nasr, Ismail; Weigel, Robert; Kissinger, Dietmar (IEEE International Microwave Symposium, 2013)
Millimeter-wave frequency-agile front-ends capable of operating at different frequency bands offer an attractive solution for multiband communications. In this paper we present a fully integrated wide-band quadrature receiver covering the two point to point communication bands from 71 to 76 GHz and 81 to 86 GHz and the automotive radar band at 77 GHz. The receiver was fabricated using a low-cost SiGe technology with an ft/fmax of 200/250 GHz. The chip contains a wide-band LNA, Wilkinson power divider, down conversion mixers, two stage polyphase network, VCO, and frequency prescaler. The VCO achieves an ultra high tuning range of 33% between 64 and 89 GHz. Each receiver path (I/Q) has a measured conversion gain between 17 to 23 dB over the operating frequency range. The receiver has a minimum NF of 8 dB, and an input referred compression point of -22 dBm. The complete chip consumes 220mA of current from a 3.3V supply. Index Terms—
elib2cris::1512001600,nasr2013

Broadband Multi-Octave Receiver from 1-32 GHz for Monolithic Integrated Vector Network Analyzers (VNA) in SiGe-Technology - Dietz, Marco; Girg, Thomas; Bauch, Andreas; Aufinger, Klaus; Hagelauer, Amelie Marietta; Kissinger, Dietmar; Weigel, Robert (European Microwave Integrated Circuits Conference, 2017)

Compact 2-28 GHz Planar Multi-Octave Bandwidth Wilkinson Power Dividers - Trenz, Florian; Hofmann, Maximilian; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (2014 IEEE MTT-S International Microwave Symposium (IMS), 2014)
In this paper, two broadband Wilkinson power dividers in microstrip technology are presented. A broadband operation from 2 to 28 GHz could be achieved by a multisectional layout. The dividers differ in the number of cascaded steps, which allows application dependent usage. Furthermore, the dividers make use of commercially available, surface mounted thinfilmresistors, allowing a straightforward implementation. The maximum occupied area is around 30mm2 for the longer version and around 16mm2 for the shorter version. Measurements show a matching better than 13 dB and an isolation of better than 10 dB over the whole frequency range. The achieved bandwidth ratio of 14:1 represents, in combination with the compact layout, the highest ratio for Wilkinson dividers published so far.
elib2cris::1512001600,trenz2014
Keywords: Wilkinson power divider; broadband

Concentration detection in water-glucose mixtures for medical applications using ultrasonic velocity measurements - Schwerthöffer, Udo; Winter, M.; Weigel, Robert; Kissinger, Dietmar (IEEE Internation Symposium on Medical Measurement and Applications, 2013)
elib2cris::1512001600,schwerthoeffer2013

Consideration of higher frequency bands in accurate millimeter-wave FMCW-radar system simulations for automotive applications - Dudek, Manuel; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (Wireless and Microwave Technology Conference, 2011)
In this paper we demonstrate the necessity of taking harmonic bands into account when performing accurate simulations for millimeter-wave frequency-modulated continuous-wave (FMCW) radar systems. Especially under nonlinear conditions when harmonics are generated and influence the signal quality of target detection the higher frequency bands cannot be neglected anymore. In ordinary complex baseband simulations, that are considered as a means to keep the amount of data low in FMCW radar simulations, previous knowledge is needed to explicitly model the impact of effects in higher frequency bands on the specific circuit. Our approach takes the effects of multiples of the actual operating frequency into account, thus enabling higher accuracy while keeping the amount of data moderate. As an example for the capability of this simulation approach a scenario is calculated showing the difference between both simulation strategies.
elib2cris::1512001600,dudek2011a

Dehydratations-Erkennung im Alltag durch integrierte nicht-invasive Sensorik - Dietz, Marco; Schmidt, Christian; Trenz, Florian; Nehring, Johannes; Hagelauer, Amelie Marietta; Weigel, Robert; Kissinger, Dietmar (Medizin Innovativ - MedTech Summit 2016, 2016)
Veränderungen im menschlichen Wasserhaushalt führen zur Verminderung der Leistungsfähigkeit im Alltag bis hin zu lebensbedrohlichen Situationen. Insbesondere hier ist eine Überwachung des menschlichen Wasserhaushaltes wichtig. Ein neuer Ansatz schafft die Möglichkeit, Nutzern auch im Alltag die aktive Überwachung ihres Hydratationszustandes zu ermöglichen. Das Verfahren beruht auf Sensorik, die als Stimulus eine elektromagnetische Welle verwendet. Aus der vom Gewebe reflektierten Welle können Rückschlüsse auf die Wasserkonzentration gezogen werden. So wird ein alltagstaugliches und hochintegriertes Detektionssystem möglich, welches vom Nutzer permanent getragen werden kann und die Analyse des Wasserhaushaltes erlaubt.
elib2cris::1512001600,dietz2016
Keywords: Dehydratation; nicht-invasive Sensorik; Gesundheitsförderung; integrierte Diagnostik

Depth and Rate of the Save - Hofmann, Maximilian; Edelmann, Jan-Christoph; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (IEEE Microwave Magazine, 2012)
Sudden cardiac arrest (SCA) is one of the leading causes of death worldwide. Studies have shown that roughly 90% of all patients suffering from SCAs die due to ventricular fibrillation. This phenomenon is best described as an electrical chaos in the myocardium leading to fast but at the same time very short movements of the muscle. This results in a total collapse of the blood circulation and after 3–5 min, the death of gray matter. Without any external help, this will lead to death. In the United States, for instance, 325,000 people are affected each year. It is indisputable that the quality of a cardiopulmonary resuscitation (CPR) can make the difference between life and death. In 2010, the European Resuscitation Council (ERC) as well as the American Heart Association (AHA) submitted official guidelines for resuscitation. According to the ERC and further research results, the basilife support can be significantly improved by a feedback system. The recommendation for CPR feedback systems has subsequently been adopted by the German Medical Association (GMA). A CPR feedback system gives a response to the first aider about the quality of the resuscitation (compression depth and rate).
elib2cris::1512001600,hofmann2012f

Design and Breakdown Behavior of 77GHz Variable Gain Power Amplifiers in SiGe- Technology - Borutta, Karl; Lämmle, Benjamin; Wagner, Christoph; Maurer, Linus; Weigel, Robert; Kissinger, Dietmar (European Microwave Conference (EuMC), 2013, 2013)
This paper presents two fully integrated differential programmable power amplifiers for automotive radar applications at 77GHz. The power amplifiers were fabricated in a silicon-germanium technology featuring bipolar transistors with an ft/fmax of 200GHz/250GHz. Measurements have been performed for different temperatures, in particular at -40°, 27° and 125°. A maximum gain of 10 dB is achieved for both amplifiers at room temperature. In addition the breakdown behavior of both amplifiers has been investigated. The building blocks of the amplifiers, which are affected by the breakdown effect had been indentified and design guidelines to avoid breakdown effects in power amplifiers are presented.
elib2cris::1512001600,borutta2013
Keywords: differential amplifiers; electric breakdown; millimetre wave bipolar transistors; millimetre wave power amplifiers; millimetre wave radar; programmable circuits; temperature measurement; Current measurement

Design of an integrated 60 GHz cross-coupled oscillator in SiGe technology - Agethen, Roman; Lämmle, Benjamin; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE Semiconductor Conference Dresden, 2011)
This paper presents the design of an integrated fully differential 60GHz voltage controlled oscillator in SiGe technology featuring f t = 200 GHz high speed bipolar HBTs. The VCO is based on a differential Colpitts VCO. The core consumes an average amount of 26mA @ 3.3V supply voltage. The tuning bandwidth is about 12%. The utilized buffer at the output consumes additional 64 mA @ 3.3V and provides an output power of 13dBm over the tuning bandwidth. The phase noise @ 1MHz is less than -75 dBc/Hz.
elib2cris::1512001600,agethen2011a

Design of Gain Optimized Broadband Low Noise Amplifiers at 120 GHz using SiGe Technology - Chakraborty, Abhiram; Kissinger, Dietmar; Lämmle, Benjamin; Hartnagel, Hans; Weigel, Robert (German Microwave Conference, 2010)
This paper presents the design of single-ended, double stage cascode low noise amplifiers at 120 GHz. A design methodology employing three techniques for gain enhancement of the LNA is presented. The effect of traditional emitter - degeneration technique and its feasibility for simultaneous noise and power matching is evaluated at 120 GHz. The LNAs are designed in a 250 GHz fT and 300 GHz fmax 0.13 μm SiGe:C BiCMOS process. By employing the three design techniques the gain of the LNA is improved by almost 3.5 dB. The two stage gain optimized LNA achieves a gain of 24 dB and a noise figure of 7.2 dB. The circuit works with a supply voltage of 3.3 V and consumes less than 40 mW of power.
elib2cris::1512001600,chakraborty2010
Keywords: BiCMOS integrated circuits; Broadband amplifiers; Low-noise amplifiers; Noise figure; wideband amplifiers; cascode low noise amplifier; emitter-degeneration technique; 120 GHz; 250 GHz; 300 GHz; noise matching; SiGe Heterojunction Bipolar Transistor

Design Techniques for Broadband Low Noise Amplifiers at 120GHz in a SiGe BiCMOS Process - Chakraborty, Abhiram; Lämmle, Benjamin; Kissinger, Dietmar (ANALOG'11 Fachtagung Entwicklung von Analogschaltungen mit CAE-Methoden, 2011)
elib2cris::1512001600,chakraborty2011

Determination of Changes in NaCl Concentration in Aqueous Solutions Using an M-Sequence Based Sensor System - Schmidt, Christian; Lübke, Maximilian; Dietz, Marco; Weigel, Robert; Kissinger, Dietmar; Hagelauer, Amelie Marietta (IEEE International Microwave Bio-Conference, 2017)

Determination of sugar concentration in aqueous solutions using ultra-wideband microwave impedance spectroscopy - Guarin Aristizabal, Gustavo Adolfo; Hofmann, Maximilian; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (IEEE MTT-S International Microwave Symposium, 2013)
elib2cris::1512001600,guarin2013

Die Zukunft der Satellitenkommunikation - Bischl, Hermann; Fuchs, Christian; Geissler, Matthias; Giggenbach, Dirk; Hein, Matthias; Jacob, Arne; Jakoby, Rolf; Kallfass, Ingmar; Kissinger, Dietmar; Martin, Siegbert; Müller, Jens; Petry, Hans-Peter; et al. (2016)
elib2cris::1512001600,bischl2016

Eine erweiterte Millimeterwellen FMCW-Radar Systemsimulationsumgebung fuer den Einsatz im Automobilbereich - Dudek, Manuel; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (ANALOG'11 Fachtagung Entwicklung von Analogschaltungen mit CAE-Methoden, 2011)
In diesem Artikel stellen wir eine Simulationsumgebung fuer Millimeterwellen FMCW-Radare fuer den Einsatz im Automobilbereich vor, die einen 3D-Kanalsimulator beinhaltet. Dafuer nutzen wir Agilent's RF Entwicklungsumgebung ADS(R) fuer die Systemsimulation und berechnen die Impulsantwort des Kanals, basierend auf den Daten die von einem 3D-Raytracer generiert werden, in einer Matlab(R) Cosimulation. Um die Rechenzeit zu reduzieren findet der gesamte Signalfluss im komplexen Basisband statt und aufwaendige Polygonmodelle werden durch ihre Streuzentrenmodelle als weitere Verbesserung substituiert. Alle Effekte in den Harmonischen Zonen, die auf Grund von Nichtlinearitaeten im Sende- oder Empfangsmodul auftreten, werden in der Simulation korrekt wiedergegeben. Um die Leistungsfähigkeit des Simulationsansatzes, was Geschwindigkeit und Genauigkeit anbelangt, zu evaluieren, wird ein typisches Verkehrsszenario simuliert.
elib2cris::1512001600,dudek2011d

Energy-efficient wireless sensing using a generic ADC sensor interface within a passive multi-standard RFID transponder - Brenk, Daniel; Essel, Jochen; Heidrich, Jürgen; Agethen, Roman; Kissinger, Dietmar; Hofer, Günter; Holweg, Gerald; Fischer, Georg; Weigel, Robert (IEEE Sensors Journal, 2011)
elib2cris::1512001600,brenk2011

Evaluation of a Reflection Based Dehydration Sensing Method for Wristwatch Integration - Trenz, Florian; Weigel, Robert; Kissinger, Dietmar (MIKON 2016 - International Conference on Microwave, Radar and Wireless Communications, 2016)
This paper presents a compact dehydration measurement method, keeping in mind a system integration in a wristwatch housing. In contrast to the conventional measurement approach using two measurement antennas, the proposed measurement setup uses only one antenna and one metallic reflector. Measurements have been performed using a patch antenna immersed in a steel basin filled with a tissue-equivalent liquid. The microstrip antenna has been optimized for an application in the 2.45GHz ISM band and features a biocompatible passivation layer and a rigid aluminum housing. The tissue-equivalent liquid mimicks dielectric tissue properties over a hypotonic hydration change. The steel basin acts as a liquid retainer and as a metallic reflector for the measurement setup. Measurements with the proposed setup have shown, that a clear distinction of physiologically relevant hydration levels is possible.
elib2cris::1512001600,trenz2016
Keywords: Biomedical measurement; Microwave sensors; Biosensors; Reflectometry

Fast and accurate design methodology for millimeter-wave integrated circuits (invited) - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Kissinger, Dietmar; Weigel, Robert (URSI General Assembly Scientific Symposium, 2011)
elib2cris::1512001600,laemmle2011

FPGA-based signal control for highly integrated 60 GHz radar distance measurements - Agethen, Roman; Pour Mousavi, Seyed Mehran; Mengs, P.; Weigel, Robert; Kissinger, Dietmar (European Radar Conference, 2013)
elib2cris::1512001600,agethen2013a

Hidden Electronics - Dudek, Damian; Fettweis, Gerhard; Frey, Lothar; Kissinger, Dietmar; Kutter, Christoph; Mathis, Wolfgang; Lugli, Paolo; Russer, Peter; Weigel, Robert; Wolff, Ingo (2015)
elib2cris::1512001600,dudek2015a

High-Linearity 77-GHz SiGe Automotive Radar Front-Ends - Kissinger, Dietmar (IEEE/MTT-S International Microwave Symposium (IMS), 2009)
The harsh automotive environment poses a series of challenging performance demands to integrated 77-GHz radar frontends. Besides a large temperature range of operation, sufficiently large output power of the transmitter and corresponding receiver sensitivity have to be guaranteed. The large dynamic range of the received signal additionally demands a highly linear behaviour of such receiver circuits. This presentation deals with the design of high-linearity integrated receiver frontends and its subcomponents for 77- GHz automotive radar applications based on high-performance SiGe technologies. These include low-noise amplifiers and down-conversion mixer circuits as well as fully integrated receiver frontends. The authors give insight to the design and measurement techniques of state-of-the-art highly linear 77-GHz radar building blocks. Different circuit architectures are investigated and the corresponding designs and performance parameters are presented.
elib2cris::1512001600,kissinger2009c

Highly sensitive microwave resonant near-field sensor for precise aqueous glucose detection in microfluidic medical applications - Schwerthöffer, Udo; Weigel, Robert; Kissinger, Dietmar (IEEE Instrumentation and Measurement Technology Conference, 2014)
elib2cris::1512001600,schwerthoeffer2014

High Speeds in a Single Chip Impact of SiGe/Si on Millimeter-Wave Devices and Applications. - Kasper, Erich; Kissinger, Dietmar; Russer, Peter; Weigel, Robert (IEEE Microwave Magazine, 2009)
elib2cris::1512001600,kasper2009

Industrial mmWave Radar Sensor in Embedded Wafer-Level BGA Packaging Technology - Beck, Christopher; Ng, Herman Jalli; Agethen, Roman; Pour Mousavi, Seyed Mehran; Forstner, Hans-Peter; Wojnowski, Maciej; Pressel, Klaus; Weigel, Robert; Hagelauer, Amelie Marietta; Kissinger, Dietmar (IEEE Sensors Journal, 2016)
We present highly integrated 60GHz radar transceivers for industrial sensor applications. The bistatic and monostatic transceivers are implemented in the SiGe bipolar technology and packaged using the embedded wafer-level ball grid array (eWLB) technology that allows for direct embedding of the antennas in the package redistribution layer. In this way, very compact and efficient radar frontends comprising all millimeter-wave components can be implemented in an 8 × 8mm2 package. These frontends were soldered on a standard low-cost PCB based on FR4 material. For verification of the proposed frontends, an FMCW radar system was developed and set up within this work. Theoretical considerations and simulations as well as corresponding measurements were carried out for the evaluation of the designed system. The demonstrator results of these embedded radar sensors show excellent system performance at a high integration level.
elib2cris::1512001600,beck2016
Keywords: SiGe RFICs; SiP modules; millimeter-wave circuits; packaging; radar systems

Integrated dielectric millimeter-wave sensors for biomedical applications (invited) - Lämmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Weigel, Robert; Kissinger, Dietmar (Analog, 2011)
elib2cris::1512001600,laemmle2011c

Integrated millimeter-wave transceiver concepts and technologies for wireless multi-Gbps communication - Kissinger, Dietmar; Girg, Thomas; Beck, Christopher; Nasr, Ismail; Forstner, Hans-Peter; Wojnowski, Maciej; Pressel, Klaus; Weigel, Robert (IEEE MTT-S International Microwave Symposium, 2015)
elib2cris::1512001600,kissinger2015a

Integrated Systems-in-Package: Heterogeneous Integration of Millimeter-Wave Active Circuits and Passives in Fan-Out Wafer-Level Packaging Technologies - Hagelauer, Amelie Marietta; Wojnowski, Maciej; Pressel, Klaus; Weigel, Robert; Kissinger, Dietmar (IEEE Microwave Magazine, 2018)
Keywords: Antenna measurements; Dipole antennas; Integrated circuits; Packaging; Radio frequency; Silicon; Transceivers

Integrated Test Concepts for In-Situ Millimeter-Wave Device Characterization - Kissinger, Dietmar; Nehring, Johannes; Bauch, Andreas; Borutta, Karl; Nasr, Ismail; Lämmle, Benjamin; Weigel, Robert (IEEE 13th International New Circuits and Systems Conference (NEWCAS), 2015)
elib2cris::1512001600,kissinger2015b

Integrated Test for Silicon Front Ends - Kissinger, Dietmar; Lämmle, Benjamin; Maurer, Linus; Weigel, Robert (IEEE Microwave Magazine, 2010)
Silicon-based technologies have enabled the monolithic integration of transceiver circuits with operational frequencies up into the millimeter-wave regime. While high integration relaxes the requirements on RF chip-to-chip interconnects and external circuitry, it imposes serious challenges upon the traceability of failure mechanisms and functional errors of the individual building blocks that comprise the front-end. Additionally, expensive external measurement equipment in combination with complex, error-prone, and time-consuming calibration procedures, necessitates the development of on-chip test modules. It has been shown that a variety of built-in test schemes are currently the topic of research for both the mixed-signal and microwave domain. Solutions for the individual building blocks that will enable direct verification of performance parameters have been presented throughout this article. Current RF transceiver architectures will require a mixture of both paradigms for successful implementation of integrated test strategies. It is the authors' belief that the application of such concepts is a must for future integrated transceiver systems to meet the stringent requirements of time-to-market and low-cost of mass market consumer products.
elib2cris::1512001600,kissinger2010b
Keywords: Circuit testing; Integrated circuit interconnections; Integrated circuit technology; Millimeter wave integrated circuits; Millimeter wave measurements; Millimeter wave technology; Monolithic integrated circuits; Radio frequency; Silicon; Transceivers

Integrierte Radar Sensoren in Silizium-Germanium Technologie für den Automobilbereich - Kissinger, Dietmar; Weigel, Robert (HF-Report, 2010)
elib2cris::1512001600,kissinger2010a

Large-signal measurements and non-linear characterization of an analog frontend for passive UHF CMOS RFID transponders - Essel, Jochen; Brenk, Daniel; Heidrich, Jürgen; Weigel, Robert; Kissinger, Dietmar (IEEE Transactions on Microwave Theory and Techniques, 2013)
elib2cris::1512001600,essel2013

Low Complexity 60-GHz Receiver Architecture for Simultaneous Phase and Amplitude Regenerative Sampling Systems - Girg, Thomas; Schrüfer, Daniel; Dietz, Marco; Hagelauer, Amelie Marietta; Kissinger, Dietmar; Weigel, Robert (International Symposium on Integrated Circuits, 2016)
With increasing data rates in communication systems, the call for wideband transceiver solutions capable of processing complex modulation schemes is getting stronger. Unfortunately, this goes along with power hungry systems and more complex integrated circuits. A novel receiver architecture, which addresses these issues, is based on the simultaneous phase and amplitude regenerative sampling system. Its system exploits switched injection-locked oscillators and their capability to regenerate signals with a gain of over 40dB. This paper demonstrates an integrated solution for phase demodulation in such an architecture. The proposed concept uses the low complex but efficient self-mixing principle and consists mainly of double-balanced Gilbert mixers, amplifiers, a delay line and passive power dividers. The detection of the phase is achieved through self-mixing the regenerated signal with one path delayed by a symbol period. The architecture achieves 2 GBaud/s with 8 th order differential phase shift keying at a frequency of 60 GHz and is realized in a 130nm SiGe BiCMOS technology.
elib2cris::1512001600,girg2016a
Keywords: SiGe; BiCMOS; simultaneous phase and amplitude regenrative sampling; high data rate; communication; self-mixing

Microwave and millimeter-wave integrated circuits MTT-6: The RF core chips of the 21st century (guest editorial) - Quay, Rainer; Kissinger, Dietmar (IEEE Microwave Magazine, 2012)
elib2cris::1512001600,quay2012

Microwave-Based Noninvasive Concentration Measurements for Biomedical Applications - Hofmann, Maximilian; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE Transactions on Microwave Theory and Techniques, 2013)
A Debye relaxation model for the permittivity of aqueous glucose solution is given up to 40GHz. Measurements of aqueous solutions are compared with invasive measurements on over 40 blood samples. Reflection and transmission based techniques are explained, concerning the application in biomedical concentration measurements. Wideband measurements on different sensing structures are introduced. Reflection and transmission based sensors are applied to a six-port reflectometer as well as a homodyne vector network analyzer (VNA).
elib2cris::1512001600,hofmann2013b

Microwave Sensor for Precise Permittivity Characterization of Liquids Used for Aqueous Glucose Detection in Medical Applications - Schwerthöffer, Udo; Weigel, Robert; Kissinger, Dietmar (German Microwave Conference 2014, 2013)
elib2cris::1512001600,schwerthoeffer2013e

Microwave wideband spectroscopy techniques targeting biomedical sensing applications - Nasr, Ismail; Hofmann, Maximilian; Radwan, Ahmed; Lämmle, Benjamin; Fischer, Georg; Kissinger, Dietmar; Weigel, Robert (Joint Symposium on Opto- and Microelectronic Devices and Circuits, 2012)
elib2cris::1512001600,nasr2012b

Millimeter Wave FMCW Radar System Simulations including a 3D Ray Tracing Channel Simulator - Dudek, Manuel; Wahl, René; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (Asia-Pacific Microwave Conference (APMC), 2010)
In this paper a millimeter-wave radar system simulation environment for frequency-modulated continuous-wave (FMCW) radar using a 3D ray tracing channel simulator is presented. Therefore we use Agilents' RF design environment ADS® for system simulation and calculate the channel impulse response based on the data received from a 3D ray tracer in a Matlab® co-simulation. To reduce computing time the whole signal flow is processed in a complex baseband representation and scattering center models are used as substitute for complex polygon targets as further improvement. Nevertheless all effects occurring at harmonic bands and at DC due to nonlinearities in the transmitter and receiver circuits are well reflected in the simulation. A typical road scenario is simulated and the results show the capabilities of the simulation technique in terms of speed and accuracy.
elib2cris::1512001600,dudek2010a
Keywords: Computational modeling; CW radar; FM radar; radar computing; ray tracing; road vehicle radar; millimeter wave radar; 3D ray tracing channel simulator; Matlab cosimulation; channel impulse response calculation; complex polygon target; frequency-modulated continuous-wave radar; millimeter-wave radar system simulation; scattering center model; RF impairments

Millimeter-wave integrated reflectometer architectures for biomedical applications - Kissinger, Dietmar; Lämmle, Benjamin; Nasr, Ismail; Weigel, Robert (IEEE Topical Conference on Biomedical Wireless Technologies, Networks and Sensing Systems, 2013)
elib2cris::1512001600,kissinger2013

Millimeter-Wave Receiver Concepts for 77 GHz Automotive Radar in Silicon-Germanium Technology - Kissinger, Dietmar (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)
elib2cris::1512001600,kissinger2012

Miniature Microwave Biosensors: Noninvasive Applications - Guarin Aristizabal, Gustavo Adolfo; Hofmann, Maximilian; Nehring, Johannes; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (IEEE Microwave Magazine, 2015)
elib2cris::1512001600,guarin2015a

Miniaturisierte Dehydratations-Sensorik im Leistungssport - Schmidt, Christian; Dietz, Marco; Trenz, Florian; Nehring, Johannes; Weigel, Robert; Kissinger, Dietmar (Fußball 4.0 - Jahrestagung der dvs-Kommission Fußball, 2015)
elib2cris::1512001600,schmidt2015

Modeling and Experimental Investigation of Microwave Cardiopulmonary Resuscitation Feedback Systems - Hofmann, Maximilian; Edelmann, Jan-Christoph; Bolz, Armin; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (The 7th German Microwave Conference (GeMiC), 2012, 2012)
This paper presents a novel scalable 3D thorax model for electromagnetic (EM) field simulations. Two antennas operating at 1.6 GHz are designed and matched for application in a cardiopulmonary resuscitation (CPR) feedback system. A microwave based CPR feedback system is investigated by applying the new thorax model. The fabricated antennas are evaluated in self-experiments. Magnitude and phase measurements are compared with simulation results. It is shown, that the thorax compression during CPR can be monitored with the proposed RF based approach with good agreement to the EM simulation.
elib2cris::1512001600,hofmann2012e
Keywords: HF antennas; biomechanics; biomedical measurement; cardiovascular system; compressibility; electromagnetic fields; feedback; antennas

Modeling and Measurement of a Tissue-Equivalent Liquid for Noninvasive Dehydration Sensing in the 2.45 GHz ISM-Band - Trenz, Florian; Kalpen, Victoria; Weigel, Robert; Kissinger, Dietmar (IEEE MTT-S International Microwave Workshop Series on RF and Wireless Technologies for Biomedical and Healthcare Applications(IMWS-Bio 2015), 2015)
In this paper, a blood-equivalent liquid is presented. The phantom material at room temperature is a valid representation of blood at body temperature in the frequency range from 2 to 3 GHz with an maximum deviation of ±1.5 in eps1 and ±2.8 in eps2 . The effect of a hypertonic variation of the plasma hydration level has been modeled by varying the amount of water ±14 % in the tissue-equivalent fluid. Transmission based measurements have been performed on a tube phantom of PMMA with narrowband patch antennas on flexible substrates. The antennas have been placed at opposite sides of the phantom and measurements have been performed at different hydration levels of the substitute liquid. A clear distinction of the levels can be seen in both magnitude and phase of the transmission coefficient.
elib2cris::1512001600,trenz2015a
Keywords: Biomedical measurement; Biomedical monitoring; Biological system modeling; Microwave sensors; Biosensors; Phantoms

Multi-Octave Planar Microwave Slot-Coupled Directional Coupler up to 28 GHz with Novel Phase Velocity Compensation - Bauch, Andreas; Hofmann, Maximilian; Weigel, Robert; Kissinger, Dietmar (European Microwave Conference 2014, 2014)
A nonuniform symmetrical QTEM-mode directional slot-line coupler operating in a multi-octave frequency range from 2.5 GHz up to 28.6 GHz is presented. The calculated continuously varying even- and odd-mode line impedances are realized by a 3D electromagnetic (EM) ﬁeld simulation of the slot-coupled microstrip cross section. A new method of even- and odd-mode phase velocity compensation, based on a continuously structured prepreg, is suggested. A -8.34 dB coupling factor is achieved, showing a low amplitude and phase imbalance up to 28 GHz. Furthermore, a tandem conﬁguration is evaluated by utilizing two -8.34 dB directional coupler to form a wideband -3.01 dB coupler.
elib2cris::1512001600,oborovski2014
Keywords: Directional Coupler; Passive Microwave Circuits; Wideband

Non-Invasive Glucose Monitoring Using Open Electromagnetic Waveguides - Hofmann, Maximilian; Bloss, M.; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (EuMA European Microwave Conference, 2012)
This paper presents a novel approach towards noninvasive glucose measurement. The introduced concept is based on an electromagnetic (EM) wave transmission along blood vessels. Theoretical investigation of a TEM wave propagation through a aqueous glucose solution is shown. The concept was evaluated by a simplified demonstrator which consists of a dielectric covered TEM-Waveguide. A 3D field simulation of the structure has been performed with a glucose dependent Debye relaxation model. The EM waveguide was fabricated and measured with various glucose concentrations. A phase difference of 12 deg for a 500mg/dl variation in glucose concentration was measured at 20GHz.
elib2cris::1512001600,hofmann2012b

Optimum Transistor Sizing for Low-Power Subthreshold Standard Cell Designs - Grimminger, Florian; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (International Semiconductor Conference Dresden Grenoble, 2012)
This paper presents a simple method for standard cell optimization in the subthreshold regime. Through proper dimensioning of the transistor length and width an improved symmetric propagation delay and a reduction in dynamic power consumption compared to conventional CMOS standard cell implementations is achieved. The performance of the presented cells has been verified using logic gate arrays and ring oscillators with high number of stages. The measurement results reasonably agree with simulation data.
elib2cris::1512001600,grimminger2012

Oxygen detection system consisting of a millimeter wave Fabry-Pérot resonator and an integrated SiGe front-end - Wecker, Julia; Kurth, Steffen; Mangalgiri, Gauri; Gaitzsch, Markus; Gessner, Thomas; Bauch, Andreas; Nasr, Ismail; Weigel, Robert; Kissinger, Dietmar; Hackner, Angelika; Prechtel, Ulrich (SPIE Photonics West, 2015)
elib2cris::1512001600,wecker2015

Positions- und Geschwindigkeitsmessung mit Mikrowellen am Beispiel Kfz-Radar - Kissinger, Dietmar; Weigel, Robert (Workshop Mikrowellenmesstechnik, 2008)
elib2cris::1512001600,kissinger2008

SiGe-based 77GHz Automotive Radar Systems - Kissinger, Dietmar (Workshop Radar, Communication and Measurement, 2009)
elib2cris::1512001600,kissinger2009b

SiGe Integrated Broadband Wireless Sensors for Biomedical Applications - Kirchner, Jens; Nehring, Johannes; Guarin Aristizabal, Gustavo Adolfo; Nasr, Ismail; Lämmle, Benjamin; Dietz, Marco; Weigel, Robert; Kissinger, Dietmar; Hagelauer, Amelie Marietta (9th Sin-German Joint Symposium on Opto- and Microelectronic Devices and Circuits (SODC2016), 2016)
elib2cris::1512001600,kirchner2016a

Single- and Dual-Port 50-100-GHz Integrated Vector Network Analyzers With On-Chip Dielectric Sensors - Nasr, Ismail; Nehring, Johannes; Aufinger, Klaus; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE Transactions on Microwave Theory and Techniques, 2014)
This work presents a single- and dual-port fully integrated millimeter-wave ultra-broadband vector network analyzer. Both circuits, realized in a commercial hbox0.35-muhbox m SiGe:C technology with an f_t/f_max of hbox170/250 GHz, cover an octave frequency bandwidth between 50–100 GHz. The presented chips can be configured to measure complex scattering parameters of external devices or determine the permittivity of different materials using an integrated millimeter-wave dielectric sensor. Both devices are based on a heterodyne architecture that achieves a receiver dynamic range of 57–72.5 dB over the complete design frequency range. Two integrated frequency synthesizer modules are included in each chip that enable the generation of the required test and local-oscillator millimeter-wave signals. A measurement 3sigma statistical phase error lower than 0.3^circ is achieved. Automated measurement of changes in the dielectric properties of different materials is demonstrated using the proposed systems. The single- and dual-port network analyzer chips have a current consumption of 600 and 700 mA, respectively, drawn from a single 3.3-V supply.
elib2cris::1512001600,nasr2014a

System Analysis of a Phased-Array Radar Applying Adaptive Beam-Control for Future Automotive Safety Applications - Dudek, Manuel; Nasr, Ismail; Bozsik, Gabor Josef; Hamouda, Mohammed; Kissinger, Dietmar; Fischer, Georg (IEEE Transactions on Vehicular Technology, 2015)
elib2cris::1512001600,dudek2015

The Impact of Antenna Characteristics on Target Signal Detection in FMCW-Radar System Simulations for Automotive Applications - Dudek, Manuel; Nasr, Ismail; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (IEEE Radio Wireless Symposium (RWS), 2012)
In this scientific paper a versatile system simulation environment is introduced that enables investigations on millimeter-wave FMCW-radar sensors. With respect to the latest developments in automotive radar the simulator combines an RF-frontend simulation engine and a 3D ray-tracing tool to take the effects of the radar channel into account. Furthermore different antenna characteristics can be generated by the phased-array radar topology implemented to examine not only the behavior of the RF-frontend but the impact of the concrete traffic situation on the whole sensor system. Therefore development engineers are actively assisted with their task to design new accurate and reliable systems, thus enabling the transition from current pure comfort systems to future systems including an increased number of safety functions. To demon-strate the usability of this advanced simulation approach for the development of future radar sensors a typical traffic scenario is calculated showing not only the impact of the antennas’ beamwidth and side-lobes on target signal detection, but also the performance of the simulation environment built-up.
elib2cris::1512001600,dudek2012

The Impact of Phase Noise Parameters on Target Signal Detection in FMCW-Radar System Simulations for Automotive Applications - Dudek, Manuel; Nasr, Ismail; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (CIE International Conference on Radar, 2011)
Accurate system simulations have proven to be a valuable aid during the development process and help to decrease the time-to-market and the amount of design iterations, thus keeping development costs at a moderate level. Therefore a frequency-modulated continuous-wave (FMCW) radar system simulation environment has been built up, enabling for performance analysis of millimeter-wave radar frontends for automotive applications. A key parameter especially for radar systems applying the FMCW principle thereby is the linearity of the frequency ramp as it directly affects the quality of the target signal and thus the performance of the entire radar sensor. Hence in this scientific paper we investigate the influence of a phase noise afflicted VCO on the target signal detection, and the range resolution respectively. Leeson’s equation is applied to model oscillator phase noise and the results show which parameters are crucial for the radar system. Eventually a two-target scenario is calculated to substantiate the statements taken.
elib2cris::1512001600,dudek2011b

The Six-Port in Modern Society - Kölpin, Alexander; Vinci, Gabor; Lämmle, Benjamin; Kissinger, Dietmar; Weigel, Robert (IEEE Microwave Magazine, 2010)
Modern wireless sensing and communication systems are often based on high bandwidth and high carrier frequencies. In the range beyond 100 GHz, common receiver architectures, like active homodyne or heterodyne receivers, have an issue with the amplification needed for mixing. Also, high bandwidth is a problem for these systems. In this context, the six-port receiver is a good alternative, just as well as for lowvolume markets. The six-port concept is based on the additive superposition of the two RF input signals using four different relative phases leading to constructive or destructive interaction. The resulting signals are directly downconverted to baseband by diode circuits operated in detector or mixing mode. The complexvalued information can be easily reconstructed from the four baseband voltages. Historic evolution leads from the reflectometer approach for an alternative vector network analyzer to receivers for sensing and communications. A recent topic is the technology gap in automotive workshops for adjusting the long-range radar sensor of a car. Here, the six-port concept as alignment tool is a good choice, because of its excellent phase resolution. Currently, the integration of the six-port receiver on a MMIC for frequencies beyond 100 GHz is the focus of current work and will be intensified in the future. Will the six-port concept replace common active homodyne and heterodyne receivers? No, but it is a serious alternative for millimeter-wave frequencies and ultrahigh-bandwidth applications in wireless sensing and communication systems. This modern concept can tap new markets for both wireless sensors and sensor networks.
elib2cris::1512001600,koelpin2010a
Keywords: Antenna measurements; Bandwidth; Baseband; Digital signal processing; Mobile radio mobility management; Receivers; Wireless sensor networks

Ultra High Speed Wireless Communication: Approaches and Ideas to Achieve Wireless 100 Gb/s Communication (W19) - Low-Power System Architectures for Future 100 Gb/s Wireless Communication Systems - Kissinger, Dietmar; Vossiek, Martin; Berroth, Manfred; Ellinger, Frank (43th European Microwave Week, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.ultrah

Ultra-wideband compressed sensing radar based on pseudo-random binary sequences - Guarin Aristizabal, Gustavo Adolfo; Gardill, Markus; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (German Microwave Conference, 2015)
elib2cris::1512001600,guarin2015

Validation of a Functional Principle for a Broadband Millimeter-Wave Power Detection Structure in a Recent BiCMOS Technology - Trenz, Florian; Weigel, Robert; Kissinger, Dietmar (IEEE Radio Frequency Integrated Circuits Symposium, 2017)
In this paper, a functional principle for a broadband thermal detector suited for a monolithical integration is shown. Two tantalum load resistors are heated by an input signal, while the temperature at a fixed distance is recorded on chip with a differential temperature sensing bridge. An integrated differential to single-ended stage amplifies the bridges differential voltage and makes an output voltage proportional to the input power of the detector available. The thermal resistance and capacitance between the load resistor and the sensing cell act as a low pass filter in the electrical regime. Based on this concept, a detector chip has been designed, which has been analyzed in thermal simulations. The realized detector has been characterized on-chip and bonded to a microwave substrate for a system performance estimation. Its input impedance is tuned to 50 Ohms and measured matching is better than -15dB from 10MHz to 43.5GHz. With a low supply voltage of 1.5V and its active area of around 80x36um2, the detector is suitable for an integrated power measurement solution.
Keywords: Detectors; Envelope detectors; Monolithic integrated circuits; BiCMOS integrated circuits; Thermodynamics

Wearables with integrated Microwave-Sensors for Internet-of-Things-Applications (IoT) in the sector of health-care: An overview - Dietz, Marco; Guarin Aristizabal, Gustavo Adolfo; Hofmann, Maximilian; Nasr, Ismail; Nehring, Johannes; Lämmle, Benjamin; Schwarzmeier, Andre; Aufinger, Klaus; Hagelauer, Amelie Marietta; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (VDE Kongress 2016: Internet der Dinge, 2016)
elib2cris::1512001600,dietz2016a

Wireless integrated sensor nodes for indoor monitoring and localization (invited) - Kissinger, Dietmar; Schwarzmeier, Andre; Grimminger, Florian; Mena-Carrillo, Juan; Weber, Werner; Hofer, Günter; Fischer, Georg; Weigel, Robert (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2015)
elib2cris::1512001600,kissinger2015

Wireless technologies for grand challenges (guest editorial) - Kissinger, Dietmar (IEEE Microwave Magazine, 2014)
elib2cris::1512001600,kissinger2014